TEORI-TEORI BIMBINGAN KONSELING DALAM PENDIDIKAN - Nugroho, Anggit Fajar (Jurnal Tawadhu, 2018)
Research on guidance and counseling in education is a very important research to do and discussed in the world of education. This is because the existence of guidance and counseling in education is a logical consequence of the nature of education itself. The theory of counseling guidance departs from the view of human nature, and is developed from the framework of thinking about the development of personality and changes in human behavior that can be understood from various models of theory. The counseling process of counseling in education is a developmental encounter in which will confront the counselor (teacher) to the individual values of the students and the possible influence of counselors on the development of individual values. The essence of counseling guidance lies in individualizing or in other words independence is the purpose of counseling. Healthy independence is manifested in the awareness of the state of being with others. It is then formed through individual interaction with the environment, and counseling guidance is responsible for developing a self-sustaining developmental environment. Therefore, in this paper will be discussed about the theories of counseling guidance in education, due to the many theories about counseling guidance, the author only take three major theories of counseling guidance is, the theory of psychoanalysis, client-centered theory, and behavioristic theory.